Greece : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that economic growth of Greece has been strong for several years, underpinned by a rapid increase in private sector credit, following the liberalization of the financial sector and the sharp drop in interest rates. In 2006, real GDP rose by an estimated 4.1 percent, driven by private domestic demand and a pickup in goods exports. The authorities have introduced a number of significant structural measures to improve product markets. These include simplified business licensing procedures for industrial firms, more flexible overtime, and liberalization of network industries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet